The effect of the halls (Collectibles) of the Iraqi National Museum in revitalizing cultural tourism - Amira Hammoud Hassan, Assistant Professor Dr. Kadim Samukh Mohsin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The museum is a way to attract tourists at the local and international levels by making it a witness to the civilizations that have passed and the record of the events that occurred. Therefore, we find this cultural facility important in preserving the various knowledge and sciences that are the product of society through centuries and years and transferring them to societies to consolidate belonging to them, where the existence of the nation and its entity are linked. Because of its culture, the museum exhibits are considered from the collections, which is the language spoken by its visitors, and the main objective of the display is to activate the cultural role of the public. The main attraction of cultural tourism through its holdings as a witness to the cultural and heritage renaissance. Museums are a cultural medium and bond with me. The human being, his history, his national affiliation, and determining the status of the civilized and international homeland.